Assessing aquitard integrity in a complex aquifer – aquitard system contaminated by chlorinated hydrocarbons. (15th March 2020) - Filippini, Maria; Parker, Beth L.; Dinelli, Enrico; Wanner, Philipp; Chapman, Steven W.; Gargini, Alessandro
Abstract: This study investigates for the first time the integrity of multiple stacked aquitards with different degrees of contaminant degradation. Aquitard integrity was assessed in a contaminated, multi-layered, alluvial aquifer-aquitard system (Ferrara, northern Italy). The system was contaminated by mixed organic contaminants of industrial origin (mostly chlorinated ethenes) that were illegally disposed in an urban dump four to five decades ago. High spatial resolution profiles of hydraulic head, geochemistry and chlorinated hydrocarbon concentrations were determined through the multi-layered system via discrete interval sampling of continuous cores and multilevel groundwater sampling, at three locations aligned along a transect adjacent to the buried waste to a maximum depth of 53 m below the water table. The profiles revealed that the two shallow aquitards had low integrity with respect to impeding downward migration of dense non-aqueous phase liquid (DNAPL), and provided little protection to the underlying aquifers against DNAPL contamination due to preferential pathways through imperceptible fractures and/or permeable micro-beds. However, both aquitards inhibited downward DNAPL migration to some extent due to DNAPL retention along its flow paths and accumulation at lower permeability interfaces, with decreasing peak concentrations at the top of successively deeper aquitard units. Moreover, both aquitards enhanced contaminant biodegradation due to the occurrence of organic rich sub-layers, influencing the contaminant plume composition, mobility and fate in the underlying and overlying aquifers. The deepest aquitard showed evidence of DNAPL accumulation at the top and slow diffusion-dominated transport consistent with 40 years of transport, suggesting higher integrity compared to the two shallower aquitards. However, the occurrence of micro-fractures and/or discontinuities in the aquitard upgradient under the dump (source) is the most likely explanation for contamination of the deepest aquifer. Analytical 1-D simulations of the diffusion profiles in the deepest aquitard revealed that DNAPL contamination down to the top of this aquitard occurred with minimal delay after DNAPL waste disposal began. The results highlight the necessity of high-resolution vertical profiling for assessing the presence of imperceptible features relevant to DNAPL migration and integrity of individual aquitards affecting organic contaminant source zone mass and phase distributions over decades. Graphical abstract: Image 1 Highlights: Organic contaminants migrated through three vertically stacked alluvial aquitards. Aquitard integrity was assessed based on high-resolution vertical profiles of data. Contaminant accumulation and retention occurred at all aquifer-aquitard interfaces. An early contamination stage controlled distribution and fate of contaminants today. Diffusion profiles were modeled to assess the first arrival of contaminants at depth.